Alkaline phosphatase activity of blood plasma during puerperal period in Surti buffaloes without and with GnRH and PGF2U treatment at day 40-42 postpartum - khasatiya, C T; Dhami, A J; Prajapati, M G; Savaliya, F P; Panchal, M T; Kavani, F S (The Indian Journal of Animal Sciences, 2011)
The postpartum period was monitored through clinical diagnosis and weekly plasma profile of alkaline phosphatase from the day of calving till 105 days postpartum without or with GnRH and PGFp. treatment (on day 40-42) in 59 Surti butfaloes. The mean plasma AKP activity on the day ofcalving in GnRH treated conceived and non-conceived buffaloes fluctuated insignificantly up to sixth week postpartum (treatment week) and thereafter linearly increased, together with initiation offollicular activity/cyclicity and pregnancy, to reach the highest values by 14th week in both the groups. The overall mean AKP activity of GnRH treated conceived animal was significantly higher than that of non-conceived animals. Among GnRH untreated (control) conceived and non-conceived groups also, the AKP activity fluctuated nonsignificantly between weeks postpartum, and the values did 110t vary between conceived and non-conceived groups at any of the intervals postpartum. Among the PGF/t. treatment and control groups, the mean AKP activity on the day of calving in conceived and non-conceived animals was relatively high, which dropped within 1-2 weeks postpartum and then linearly increased to reach highest values by 15th week postpartum only in conceived animal!;;. Further, significant differences were observed between PGFp.. treated conceived and non-conceived animals at 5th, 9th and 12th to 14th week postpartum including overall mean values being higher in conceived animals and so also was the trcnd Il)r the values of PGF,ex. control conccived than non-conceived animals. Overall, the mean AKP activ ity was significantly higher in PGF,a (suboestrus) group as compared to GnRH (anoestrus) group and also in conceived than non-conceived buffaloes ofb;)th GnRH and POF2u group suggesting its role in reproduction. As regards response to GnRH treatment. 88.88% of treated buffaloes responded and came in oestrus and 85.50% of them conceived within 105 days postpartum, in contrast to GnRH control group, where 58.33% buffaloes conceived 32.14 ± 9.03 days 1rom schedule date of treatment. In PGF,u group, 83.33(% treated buBilloes responded with normal oestrus signs at a mean interval of 4.07 ± 0.53 days and al( of them (100%) conceived within 105 days postpartum (2 cycles post-treatment), in contrast to PGFp. control group, wherein 45.45% buffaloes conceived 13.40 ± 6.76 days from schedule date. The conception rate at induced oestrus in GnRH and PGFp treatment groups was 75.00 and 73.33%, respectively, suggesting their distinct beneficial role at day 40-42 postpartum.